Kingella kingae Surface Polysaccharides Promote Resistance to Neutrophil Phagocytosis and Killing - Vanessa L. Muñoz; Eric A. Porsch; Joseph W. St. Geme (mBio, 2019)
ABSTRACT Bacterial pathogens have evolved strategies that enable them to evade neutrophil-mediated killing. The Gram-negative coccobacillus Kingella kingae is an emerging pediatric pathogen and is increasingly recognized as a common etiological agent of osteoarticular infections and bacteremia in young children. K. kingae produces a polysaccharide capsule and an exopolysaccharide, both of which are important for protection against complement-mediated lysis and are required for full virulence in an infant rat model of infection. In this study, we examined the role of the K. kingae polysaccharide capsule and exopolysaccharide in protection against neutrophil killing. In experiments with primary human neutrophils, we found that the capsule interfered with the neutrophil oxidative burst response and prevented neutrophil binding of K. kingae but had no effect on neutrophil internalization of K. kingae. In contrast, the exopolysaccharide resisted the bactericidal effects of antimicrobial peptides and efficiently blocked neutrophil phagocytosis of K. kingae. This work demonstrates that the K. kingae polysaccharide capsule and exopolysaccharide promote evasion of neutrophil-mediated killing through distinct yet complementary mechanisms, providing additional support for the K. kingae surface polysaccharides as potential vaccine antigens. In addition, these studies highlight a novel interplay between a bacterial capsule and a bacterial exopolysaccharide and reveal new properties for a bacterial exopolysaccharide, with potential applicability to other bacterial pathogens. IMPORTANCE Kingella kingae is a Gram-negative commensal in the oropharynx and represents a leading cause of joint and bone infections in young children. The mechanisms by which K. kingae evades host innate immunity during pathogenesis of disease remain poorly understood. In this study, we established that the K. kingae polysaccharide capsule and exopolysaccharide function independently to protect K. kingae against reactive oxygen species (ROS) production, neutrophil phagocytosis, and antimicrobial peptides. These results demonstrate the intricacies of K. kingae innate immune evasion and provide valuable information that may facilitate development of a polysaccharide-based vaccine against K. kingae.